2021
DOI: 10.1155/2021/4614185
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Glandular Triton Tumor Arising in the Radial Nerve with Prolonged Survival: A Case Report and Review of the Literature

Abstract: Divergent differentiation is a well-known phenomenon in malignant peripheral nerve sheath tumors (MPNST) which occurs approximately in 15% of these tumors, usually towards mesenchymal elements. Differentiation towards epithelial components, however, is quite uncommon, and even exceptionally rare is concomitant mesenchymal and glandular differentiation. To our knowledge, only 14 cases of MPNST with both mesenchymal (rhabdomyoblastic) and glandular differentiation had been reported, and only two of these tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A range of cases presentation in the literature we reviewed describe the imaging manifestations (including CT and MRI) correlated with MTT: giant lump, heterogeneity, irregular margins, intratumoral hemorrhage, necrosis, lobulation, calcifications, heterogenous enhancement on postcontrast CT or MRI, hypointense/isointense T1WI and hyperintense T2WI signal on MRI, and diffusion restriction on DWI and ADC 1,8–32,39,40 . Zain et al 20 and Li et al 29 had reported similar conclusions, Li et al pointed out some characteristics common to MTTs and MPNSTs, including ill‐defined margin, intratumoral lobulation, peripheral edema, calcifications, and destruction of adjacent bone tissues.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A range of cases presentation in the literature we reviewed describe the imaging manifestations (including CT and MRI) correlated with MTT: giant lump, heterogeneity, irregular margins, intratumoral hemorrhage, necrosis, lobulation, calcifications, heterogenous enhancement on postcontrast CT or MRI, hypointense/isointense T1WI and hyperintense T2WI signal on MRI, and diffusion restriction on DWI and ADC 1,8–32,39,40 . Zain et al 20 and Li et al 29 had reported similar conclusions, Li et al pointed out some characteristics common to MTTs and MPNSTs, including ill‐defined margin, intratumoral lobulation, peripheral edema, calcifications, and destruction of adjacent bone tissues.…”
Section: Discussionmentioning
confidence: 71%
“…We compiled data on reported cases of MTT in the recent 6 years (2018–2023, Table 1). 1,6–38 There were totally 37 cases with a mean age of 39.4 years (range 8 months old–75 years old), including 24 male and 13 female patients. Eleven cases originated in the abdomen (30%), 10 cases in the head and neck (27%), 8 cases in the thoracic cavity (21%), 6 cases in the limbs (16%), 1 case in the spine (3%), and 1 case in the buttocks (3%).…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Only a few reports have described such occurrences and suggested different hypotheses. [12][13][14] The glandular elements have been suggested to originate from skin entrapment. 15 Other potential reasons behind the origin of these glandular structures is metaplasia 11 or the glands being induced by the tumor from pluripotential neural crest cells rather than being entrapped.…”
Section: Discussionmentioning
confidence: 99%